Nanocrystalline silicon carbide films for solar cells - Vlaskina, S.I.; Mishinova, V.I.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Nanocrystalline silicon carbide (nc-SiC) films as protective coating and as solar cell material for a harsh environment, high temperatures, light intensities and radiation, were investigated. p- and n-types 100-mm silicon wafers with (100) orientation were used as substrates for SiC films deposition. The films were deposited using HighFrequency Plasma Enhanced Chemical Vapor Deposition (HF-PECVD) with CH₃SiCl₃ gas as a silicon and carbon source. Hydrogen supplied CH₃SiCl₃ molecules in the field of HF discharge. Deposition was carried out on a cold substrate. The power density was 12.7 W/cm². Deposition conditions were explored to prepare films with a controlled band gap and a low defect density. Formation of nc-3C-SiC films has been confirmed by the high resolution-transmission electron microscopy analysis, optical band gap values ETauc, conductivity, charge carrier activation energy and Hall measurements. The efficiency of photoconductivity was calculated for evaluating the photoconductivity properties and for the correlations with technology. For p-n junction creation in solar cell fabrication, the ntypes nc-SiC films were doped with Al. Employing Al as a doping material of nc-n-SiC, the open-circuit voltage as high as 1.43 V has been achieved.